src/HOL/Log.thy
author huffman
Fri Mar 30 12:32:35 2012 +0200 (2012-03-30)
changeset 47220 52426c62b5d0
parent 45930 2a882ef2cd73
child 47593 69f0af2b7d54
permissions -rw-r--r--
replace lemmas eval_nat_numeral with a simpler reformulation
     1 (*  Title       : Log.thy
     2     Author      : Jacques D. Fleuriot
     3                   Additional contributions by Jeremy Avigad
     4     Copyright   : 2000,2001 University of Edinburgh
     5 *)
     6 
     7 header{*Logarithms: Standard Version*}
     8 
     9 theory Log
    10 imports Transcendental
    11 begin
    12 
    13 definition
    14   powr  :: "[real,real] => real"     (infixr "powr" 80) where
    15     --{*exponentation with real exponent*}
    16   "x powr a = exp(a * ln x)"
    17 
    18 definition
    19   log :: "[real,real] => real" where
    20     --{*logarithm of @{term x} to base @{term a}*}
    21   "log a x = ln x / ln a"
    22 
    23 
    24 
    25 lemma powr_one_eq_one [simp]: "1 powr a = 1"
    26 by (simp add: powr_def)
    27 
    28 lemma powr_zero_eq_one [simp]: "x powr 0 = 1"
    29 by (simp add: powr_def)
    30 
    31 lemma powr_one_gt_zero_iff [simp]: "(x powr 1 = x) = (0 < x)"
    32 by (simp add: powr_def)
    33 declare powr_one_gt_zero_iff [THEN iffD2, simp]
    34 
    35 lemma powr_mult: 
    36       "[| 0 < x; 0 < y |] ==> (x * y) powr a = (x powr a) * (y powr a)"
    37 by (simp add: powr_def exp_add [symmetric] ln_mult right_distrib)
    38 
    39 lemma powr_gt_zero [simp]: "0 < x powr a"
    40 by (simp add: powr_def)
    41 
    42 lemma powr_ge_pzero [simp]: "0 <= x powr y"
    43 by (rule order_less_imp_le, rule powr_gt_zero)
    44 
    45 lemma powr_not_zero [simp]: "x powr a \<noteq> 0"
    46 by (simp add: powr_def)
    47 
    48 lemma powr_divide:
    49      "[| 0 < x; 0 < y |] ==> (x / y) powr a = (x powr a)/(y powr a)"
    50 apply (simp add: divide_inverse positive_imp_inverse_positive powr_mult)
    51 apply (simp add: powr_def exp_minus [symmetric] exp_add [symmetric] ln_inverse)
    52 done
    53 
    54 lemma powr_divide2: "x powr a / x powr b = x powr (a - b)"
    55   apply (simp add: powr_def)
    56   apply (subst exp_diff [THEN sym])
    57   apply (simp add: left_diff_distrib)
    58 done
    59 
    60 lemma powr_add: "x powr (a + b) = (x powr a) * (x powr b)"
    61 by (simp add: powr_def exp_add [symmetric] left_distrib)
    62 
    63 lemma powr_mult_base:
    64   "0 < x \<Longrightarrow>x * x powr y = x powr (1 + y)"
    65 using assms by (auto simp: powr_add)
    66 
    67 lemma powr_powr: "(x powr a) powr b = x powr (a * b)"
    68 by (simp add: powr_def)
    69 
    70 lemma powr_powr_swap: "(x powr a) powr b = (x powr b) powr a"
    71 by (simp add: powr_powr mult_commute)
    72 
    73 lemma powr_minus: "x powr (-a) = inverse (x powr a)"
    74 by (simp add: powr_def exp_minus [symmetric])
    75 
    76 lemma powr_minus_divide: "x powr (-a) = 1/(x powr a)"
    77 by (simp add: divide_inverse powr_minus)
    78 
    79 lemma powr_less_mono: "[| a < b; 1 < x |] ==> x powr a < x powr b"
    80 by (simp add: powr_def)
    81 
    82 lemma powr_less_cancel: "[| x powr a < x powr b; 1 < x |] ==> a < b"
    83 by (simp add: powr_def)
    84 
    85 lemma powr_less_cancel_iff [simp]: "1 < x ==> (x powr a < x powr b) = (a < b)"
    86 by (blast intro: powr_less_cancel powr_less_mono)
    87 
    88 lemma powr_le_cancel_iff [simp]: "1 < x ==> (x powr a \<le> x powr b) = (a \<le> b)"
    89 by (simp add: linorder_not_less [symmetric])
    90 
    91 lemma log_ln: "ln x = log (exp(1)) x"
    92 by (simp add: log_def)
    93 
    94 lemma DERIV_log: assumes "x > 0" shows "DERIV (\<lambda>y. log b y) x :> 1 / (ln b * x)"
    95 proof -
    96   def lb \<equiv> "1 / ln b"
    97   moreover have "DERIV (\<lambda>y. lb * ln y) x :> lb / x"
    98     using `x > 0` by (auto intro!: DERIV_intros)
    99   ultimately show ?thesis
   100     by (simp add: log_def)
   101 qed
   102 
   103 lemmas DERIV_log[THEN DERIV_chain2, THEN DERIV_cong, DERIV_intros]
   104 
   105 lemma powr_log_cancel [simp]:
   106      "[| 0 < a; a \<noteq> 1; 0 < x |] ==> a powr (log a x) = x"
   107 by (simp add: powr_def log_def)
   108 
   109 lemma log_powr_cancel [simp]: "[| 0 < a; a \<noteq> 1 |] ==> log a (a powr y) = y"
   110 by (simp add: log_def powr_def)
   111 
   112 lemma log_mult: 
   113      "[| 0 < a; a \<noteq> 1; 0 < x; 0 < y |]  
   114       ==> log a (x * y) = log a x + log a y"
   115 by (simp add: log_def ln_mult divide_inverse left_distrib)
   116 
   117 lemma log_eq_div_ln_mult_log: 
   118      "[| 0 < a; a \<noteq> 1; 0 < b; b \<noteq> 1; 0 < x |]  
   119       ==> log a x = (ln b/ln a) * log b x"
   120 by (simp add: log_def divide_inverse)
   121 
   122 text{*Base 10 logarithms*}
   123 lemma log_base_10_eq1: "0 < x ==> log 10 x = (ln (exp 1) / ln 10) * ln x"
   124 by (simp add: log_def)
   125 
   126 lemma log_base_10_eq2: "0 < x ==> log 10 x = (log 10 (exp 1)) * ln x"
   127 by (simp add: log_def)
   128 
   129 lemma log_one [simp]: "log a 1 = 0"
   130 by (simp add: log_def)
   131 
   132 lemma log_eq_one [simp]: "[| 0 < a; a \<noteq> 1 |] ==> log a a = 1"
   133 by (simp add: log_def)
   134 
   135 lemma log_inverse:
   136      "[| 0 < a; a \<noteq> 1; 0 < x |] ==> log a (inverse x) = - log a x"
   137 apply (rule_tac a1 = "log a x" in add_left_cancel [THEN iffD1])
   138 apply (simp add: log_mult [symmetric])
   139 done
   140 
   141 lemma log_divide:
   142      "[|0 < a; a \<noteq> 1; 0 < x; 0 < y|] ==> log a (x/y) = log a x - log a y"
   143 by (simp add: log_mult divide_inverse log_inverse)
   144 
   145 lemma log_less_cancel_iff [simp]:
   146      "[| 1 < a; 0 < x; 0 < y |] ==> (log a x < log a y) = (x < y)"
   147 apply safe
   148 apply (rule_tac [2] powr_less_cancel)
   149 apply (drule_tac a = "log a x" in powr_less_mono, auto)
   150 done
   151 
   152 lemma log_inj: assumes "1 < b" shows "inj_on (log b) {0 <..}"
   153 proof (rule inj_onI, simp)
   154   fix x y assume pos: "0 < x" "0 < y" and *: "log b x = log b y"
   155   show "x = y"
   156   proof (cases rule: linorder_cases)
   157     assume "x < y" hence "log b x < log b y"
   158       using log_less_cancel_iff[OF `1 < b`] pos by simp
   159     thus ?thesis using * by simp
   160   next
   161     assume "y < x" hence "log b y < log b x"
   162       using log_less_cancel_iff[OF `1 < b`] pos by simp
   163     thus ?thesis using * by simp
   164   qed simp
   165 qed
   166 
   167 lemma log_le_cancel_iff [simp]:
   168      "[| 1 < a; 0 < x; 0 < y |] ==> (log a x \<le> log a y) = (x \<le> y)"
   169 by (simp add: linorder_not_less [symmetric])
   170 
   171 
   172 lemma powr_realpow: "0 < x ==> x powr (real n) = x^n"
   173   apply (induct n, simp)
   174   apply (subgoal_tac "real(Suc n) = real n + 1")
   175   apply (erule ssubst)
   176   apply (subst powr_add, simp, simp)
   177 done
   178 
   179 lemma powr_realpow2: "0 <= x ==> 0 < n ==> x^n = (if (x = 0) then 0
   180   else x powr (real n))"
   181   apply (case_tac "x = 0", simp, simp)
   182   apply (rule powr_realpow [THEN sym], simp)
   183 done
   184 
   185 lemma root_powr_inverse:
   186   "0 < n \<Longrightarrow> 0 < x \<Longrightarrow> root n x = x powr (1/n)"
   187 by (auto simp: root_def powr_realpow[symmetric] powr_powr)
   188 
   189 lemma ln_powr: "0 < x ==> 0 < y ==> ln(x powr y) = y * ln x"
   190 by (unfold powr_def, simp)
   191 
   192 lemma log_powr: "0 < x ==> 0 \<le> y ==> log b (x powr y) = y * log b x"
   193   apply (case_tac "y = 0")
   194   apply force
   195   apply (auto simp add: log_def ln_powr field_simps)
   196 done
   197 
   198 lemma log_nat_power: "0 < x ==> log b (x^n) = real n * log b x"
   199   apply (subst powr_realpow [symmetric])
   200   apply (auto simp add: log_powr)
   201 done
   202 
   203 lemma ln_bound: "1 <= x ==> ln x <= x"
   204   apply (subgoal_tac "ln(1 + (x - 1)) <= x - 1")
   205   apply simp
   206   apply (rule ln_add_one_self_le_self, simp)
   207 done
   208 
   209 lemma powr_mono: "a <= b ==> 1 <= x ==> x powr a <= x powr b"
   210   apply (case_tac "x = 1", simp)
   211   apply (case_tac "a = b", simp)
   212   apply (rule order_less_imp_le)
   213   apply (rule powr_less_mono, auto)
   214 done
   215 
   216 lemma ge_one_powr_ge_zero: "1 <= x ==> 0 <= a ==> 1 <= x powr a"
   217   apply (subst powr_zero_eq_one [THEN sym])
   218   apply (rule powr_mono, assumption+)
   219 done
   220 
   221 lemma powr_less_mono2: "0 < a ==> 0 < x ==> x < y ==> x powr a <
   222     y powr a"
   223   apply (unfold powr_def)
   224   apply (rule exp_less_mono)
   225   apply (rule mult_strict_left_mono)
   226   apply (subst ln_less_cancel_iff, assumption)
   227   apply (rule order_less_trans)
   228   prefer 2
   229   apply assumption+
   230 done
   231 
   232 lemma powr_less_mono2_neg: "a < 0 ==> 0 < x ==> x < y ==> y powr a <
   233     x powr a"
   234   apply (unfold powr_def)
   235   apply (rule exp_less_mono)
   236   apply (rule mult_strict_left_mono_neg)
   237   apply (subst ln_less_cancel_iff)
   238   apply assumption
   239   apply (rule order_less_trans)
   240   prefer 2
   241   apply assumption+
   242 done
   243 
   244 lemma powr_mono2: "0 <= a ==> 0 < x ==> x <= y ==> x powr a <= y powr a"
   245   apply (case_tac "a = 0", simp)
   246   apply (case_tac "x = y", simp)
   247   apply (rule order_less_imp_le)
   248   apply (rule powr_less_mono2, auto)
   249 done
   250 
   251 lemma ln_powr_bound: "1 <= x ==> 0 < a ==> ln x <= (x powr a) / a"
   252   apply (rule mult_imp_le_div_pos)
   253   apply (assumption)
   254   apply (subst mult_commute)
   255   apply (subst ln_powr [THEN sym])
   256   apply auto
   257   apply (rule ln_bound)
   258   apply (erule ge_one_powr_ge_zero)
   259   apply (erule order_less_imp_le)
   260 done
   261 
   262 lemma ln_powr_bound2:
   263   assumes "1 < x" and "0 < a"
   264   shows "(ln x) powr a <= (a powr a) * x"
   265 proof -
   266   from assms have "ln x <= (x powr (1 / a)) / (1 / a)"
   267     apply (intro ln_powr_bound)
   268     apply (erule order_less_imp_le)
   269     apply (rule divide_pos_pos)
   270     apply simp_all
   271     done
   272   also have "... = a * (x powr (1 / a))"
   273     by simp
   274   finally have "(ln x) powr a <= (a * (x powr (1 / a))) powr a"
   275     apply (intro powr_mono2)
   276     apply (rule order_less_imp_le, rule assms)
   277     apply (rule ln_gt_zero)
   278     apply (rule assms)
   279     apply assumption
   280     done
   281   also have "... = (a powr a) * ((x powr (1 / a)) powr a)"
   282     apply (rule powr_mult)
   283     apply (rule assms)
   284     apply (rule powr_gt_zero)
   285     done
   286   also have "(x powr (1 / a)) powr a = x powr ((1 / a) * a)"
   287     by (rule powr_powr)
   288   also have "... = x"
   289     apply simp
   290     apply (subgoal_tac "a ~= 0")
   291     using assms apply auto
   292     done
   293   finally show ?thesis .
   294 qed
   295 
   296 lemma tendsto_powr [tendsto_intros]:
   297   "\<lbrakk>(f ---> a) F; (g ---> b) F; 0 < a\<rbrakk> \<Longrightarrow> ((\<lambda>x. f x powr g x) ---> a powr b) F"
   298   unfolding powr_def by (intro tendsto_intros)
   299 
   300 (* FIXME: generalize by replacing d by with g x and g ---> d? *)
   301 lemma tendsto_zero_powrI:
   302   assumes "eventually (\<lambda>x. 0 < f x ) F" and "(f ---> 0) F"
   303   assumes "0 < d"
   304   shows "((\<lambda>x. f x powr d) ---> 0) F"
   305 proof (rule tendstoI)
   306   fix e :: real assume "0 < e"
   307   def Z \<equiv> "e powr (1 / d)"
   308   with `0 < e` have "0 < Z" by simp
   309   with assms have "eventually (\<lambda>x. 0 < f x \<and> dist (f x) 0 < Z) F"
   310     by (intro eventually_conj tendstoD)
   311   moreover
   312   from assms have "\<And>x. 0 < x \<and> dist x 0 < Z \<Longrightarrow> x powr d < Z powr d"
   313     by (intro powr_less_mono2) (auto simp: dist_real_def)
   314   with assms `0 < e` have "\<And>x. 0 < x \<and> dist x 0 < Z \<Longrightarrow> dist (x powr d) 0 < e"
   315     unfolding dist_real_def Z_def by (auto simp: powr_powr)
   316   ultimately
   317   show "eventually (\<lambda>x. dist (f x powr d) 0 < e) F" by (rule eventually_elim1)
   318 qed
   319 
   320 lemma tendsto_neg_powr:
   321   assumes "s < 0" and "real_tendsto_inf f F"
   322   shows "((\<lambda>x. f x powr s) ---> 0) F"
   323 proof (rule tendstoI)
   324   fix e :: real assume "0 < e"
   325   def Z \<equiv> "e powr (1 / s)"
   326   from assms have "eventually (\<lambda>x. Z < f x) F" by (simp add: real_tendsto_inf_def)
   327   moreover
   328   from assms have "\<And>x. Z < x \<Longrightarrow> x powr s < Z powr s"
   329     by (auto simp: Z_def intro!: powr_less_mono2_neg)
   330   with assms `0 < e` have "\<And>x. Z < x \<Longrightarrow> dist (x powr s) 0 < e"
   331     by (simp add: powr_powr Z_def dist_real_def)
   332   ultimately
   333   show "eventually (\<lambda>x. dist (f x powr s) 0 < e) F" by (rule eventually_elim1)
   334 qed
   335 
   336 end